1979
DOI: 10.1111/j.1365-2125.1979.tb04771.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of methyldopa and labetalol in the treatment of hypertension.

Abstract: 1 Twenty patients with essential hypertension completed a double-blind, dose-tritrated, cross-over comparison of methyldopa and labetalol. 2 Average lying BPs (systolic/diastolic) were reduced by 28/15 mmHg with methyldopa and by 23/15 mmHg with labetalol. 3 Average standing BPs (systolic/diastolic) were reduced by 29/14 mmHg with methyldopa and by 29/15 mmHg with labetalol. 4 Both lying and standing heart rates were reduced with labetalol. 5 It is concluded that the antihypertensive properties of labetalol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…[15][16][17][18][19][20] Although all were of low quality and underpowered to examine substantive perinatal and maternal outcomes, the point estimates were >1 for maternal and perinatal outcomes, suggesting that methyldopa is more likely to be worse (and not better) than labetalol. Data from outside pregnancy are limited and remote in time (1975-92); two of each of three observational studies [21][22][23] and three RCTs [24][25][26] found methyldopa and labetalol to be similarly effective for lowering BP.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Although all were of low quality and underpowered to examine substantive perinatal and maternal outcomes, the point estimates were >1 for maternal and perinatal outcomes, suggesting that methyldopa is more likely to be worse (and not better) than labetalol. Data from outside pregnancy are limited and remote in time (1975-92); two of each of three observational studies [21][22][23] and three RCTs [24][25][26] found methyldopa and labetalol to be similarly effective for lowering BP.…”
Section: Discussionmentioning
confidence: 99%
“…In present study the average dose of labetalol required to achieve optimal B.P control was much less than in above mentioned study, but for methyldopa doses were comparable. 10 Lardoux's group found that the average daily dose of labetalol required for satisfactory blood pressure control was 600 mg. 12 In the present study, 9 patients in group A (33.33%) went in spontaneous labour while 18 patients (66.67%) were induced. In group B, 23 patients (48.94%) went in spontaneous labour and 24 patient's (51.06%) were induced.…”
mentioning
confidence: 99%
“…There have been reports of positive antinuclear factor (ANF) titre in patients receiving labetalol but it is doubtful if the incidence is any greater than in the untreated state (Sanders et al, 1979a). It should be noted that 3% of untreated patients have a positive antinuclear factor, whereas the incidence on methyldopa was 13% (Wilson et al, 1978).…”
Section: Side-effectsmentioning
confidence: 97%